2011
DOI: 10.1007/s12639-011-0063-2
|View full text |Cite
|
Sign up to set email alerts
|

Parasitological and clinico-epidemiological features of onchocerciasis in West Wellega, Ethiopia

Abstract: Onchocerciasis is a disease of public health and socio-economic importance in Ethiopia. The aim of this study was to assess parasitological and clinico-epidemiological features of onchocerciasis in the Anfilo District, West Wellega, prior to implementation of Community Directed Treatment with Ivermectin (CDTI) to generate epidemiological and parasitological data for use in control program of the disease and subsequent evaluation of CDTI. A cross-sectional study was conducted in Anfilo District of West Wellega … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 15 publications
4
13
2
Order By: Relevance
“…Similarly, individuals whose age was 45 years and above were nearly ten times more likely to develop the infection as compared to individuals in the age group of 15-24 years. The finding was in agreement with findings of studies conducted in Jimma zone, West Welega zone, Nigeria, Equatorial Guinea, and Senegal where age was independently associated with onchocerciasis infection [9,13,[15][16][17][18]. This might be due to the fact that adults are most of the time engaged in outdoor activities where they can be bitten by black fly.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similarly, individuals whose age was 45 years and above were nearly ten times more likely to develop the infection as compared to individuals in the age group of 15-24 years. The finding was in agreement with findings of studies conducted in Jimma zone, West Welega zone, Nigeria, Equatorial Guinea, and Senegal where age was independently associated with onchocerciasis infection [9,13,[15][16][17][18]. This might be due to the fact that adults are most of the time engaged in outdoor activities where they can be bitten by black fly.…”
Section: Discussionsupporting
confidence: 92%
“…The finding was consistent with the findings of studies conducted in southwest Ethiopia, Cameroon, Senegal, and Equatorial Guinea [10,[12][13][14][15][16]. The study was not consistent with the studies done at Jimma zone and West Welega zone which showed the prevalence of 22.5% and 74.8%, respectively [9,17]. This difference might be attributed to difference in coverage of community directed ivermectin treatment.…”
Section: Discussionsupporting
confidence: 75%
“…In the current study, the overall prevalence rate of O. volvulus infection was 22.5 %. This finding was lower compared to the results of other studies conducted in Teppi [ 4 , 14 ] southwestern Ethiopia, around Blue Nile River [ 15 ] and West Wellega [ 16 ].The difference might be due to long time endemicity of the parasite in the mentioned study area and the higher abundance of vectors in those areas compared to the new emerging foci in the current study. Moreover, Teppi area is known for its large coffee farm and there are many daily laborers who came from different parts of the country and are engaged in outdoor activities and are at the same time exposed to simulium bite.…”
Section: Discussioncontrasting
confidence: 85%
“…In a previous study conducted in four different villages of Anfilo District, Kelem Wollega Zone, Western Ethiopia or the current study area, the average prevalence of Onchocerciasis was 74.8%. Among the villages 87.6% was recorded in Yeli, which is the highest ever recorded in Ethiopia [ 6 ].…”
Section: Introductionmentioning
confidence: 99%